Revisiting the footprints of climate change in Arctic marine food webs: An assessment of knowledge gained since 2010 - Brandt, Sören; Wassmann, Paul; Piepenburg, Dieter (Frontiers in Marine Science, 2023)
In 2011, a first comprehensive assessment of the footprints of climate change on Arctic marine ecosystems (such as altered distribution ranges, abundances, growth and body conditions, behaviours and phenologies, as well as community and regime shifts) was published. Here, we re-assess the climate-driven impacts reported since then, to elucidate to which extent and how observed ecological footprints have changed in the following decade (2011 to 2021). In total, 98 footprints have been described and analysed. Most of those impacts reported in the 2011 assessment are reconfirmed and can, hence, be assumed as continuing trends. In addition, novel footprints (behavioural changes, diet changes, altered competition and pathogen load) are described. As in 2011, most reported footprints are related to changes in distribution ranges, abundances, biomass and production. Range shifts have mostly been observed for fish species, while behavioural changes have mainly been reported for mammals. Primary production has been observed to further increase in Arctic seas. The footprints on pelagic herbivores, particularly the key species Calanus spp., are less clear. In comparison to 2011, more complex, cascading effects of climate change, such as increased bowhead whale body conditions due to increased primary production, have been reported. The observed footprints, and the trends that they indicate, strongly suggest that due to further northward range shifts of sub-Arctic and boreal species Arctic seas are likely to experience increasing species richness in the future. However, a tipping point may be reached, characterized by subsequent biodiversity decline, when Arctic-endemic species will go extinct as ocean warming and/or acidification will exceed their physiological adaptation capacity.Overall, the future Arctic Ocean will very likely experience increasing numbers and intensities of climate-change footprints.